2014
DOI: 10.1021/tx500211x
|View full text |Cite
|
Sign up to set email alerts
|

Ginger Compound [6]-Shogaol and Its Cysteine-Conjugated Metabolite (M2) Activate Nrf2 in Colon Epithelial Cells in Vitro and in Vivo

Abstract: In this study, we identified Nrf2 as a molecular target of [6]-shogaol (6S), a bioactive compound isolated from ginger, in colon epithelial cells in vitro and in vivo. Following 6S treatment of HCT-116 cells, the intracellular GSH/GSSG ratio was initially diminished but was then elevated above the basal level. Intracellular reactive oxygen species (ROS) correlated inversely with the GSH/GSSG ratio. Further analysis using gene microarray showed that 6S upregulated the expression of Nrf2 target genes (AKR1B10, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 77 publications
2
52
0
1
Order By: Relevance
“…27 In the current study, we found that 6S (1) is even more active than SFN (2.40 vs. 2.03 times higher than vehicle) (Figure 1), a well-known potent activator of Nrf2. 37,38 Using quantitative microscopy, we showed GFP fluorescence intensity at the olfactory sensory neural epithelia of 6S-treated zebrafish embryos is stronger than those of SFN-treated individuals ( Figure 2).…”
Section: Potency Of 6s Derivatives To Activate Nrf2 In Transgenic Zebsupporting
confidence: 54%
See 3 more Smart Citations
“…27 In the current study, we found that 6S (1) is even more active than SFN (2.40 vs. 2.03 times higher than vehicle) (Figure 1), a well-known potent activator of Nrf2. 37,38 Using quantitative microscopy, we showed GFP fluorescence intensity at the olfactory sensory neural epithelia of 6S-treated zebrafish embryos is stronger than those of SFN-treated individuals ( Figure 2).…”
Section: Potency Of 6s Derivatives To Activate Nrf2 In Transgenic Zebsupporting
confidence: 54%
“…25 In a recent study, we identified [6]-shogaol (6S), a major component of dry ginger, as an activator of Nrf2 in colon epithelial cells in vitro and in vivo. 26 Our data obtained with gene expression profiling, Western blotting and immunostaining clearly demonstrated that 6S induced nuclear translocation of Nrf2 and activated Nrf2 target genes in an Nrf2-dependent manner. 27 With an α,β-unsaturated carbonyl group in the alkyl tail, 6S is a typical Michael acceptor.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…The pleasurable aroma of ginger is from the constituents present in the volatile oil, while the non-volatile pungent phytochemicals of ginger consisting of gingerols, shogaols, paradols, and zingerone give the warm pungent sensation and are also reported to account for the most of its pharmacological effects 12,13 . Activation of Nrf2 in epithelial cells, HepG2 cells and HEK293 cells by 6-S was disclosed recently [22][23][24] . Of all the gingerols, the compound 6-gingerol (6-G, Fig.…”
Section: Introductionmentioning
confidence: 99%